A 'Proper Night Out': A Practice Theory Exploration of Gendered Drinking. (June 2023) - Hennell, Kath; Limmer, Mark; Piacentini, Maria
Drawing on the three-element model of social practice theory and key conceptualisations relating to gender performance, this article reports on an empirical study of the intersecting practices of drinking alcohol and doing gender. We present data from a 14-month research project to explore the online and offline intoxicated drinking practices of 23 young people in England framed as a 'proper night out'. The data were analysed with a focus on three elements (the 'corporeal', 'alcohol', and 'caring'), and the findings demonstrate how young people collectively practice gender through their intoxicated drinking practices. This operationalisation of practice theory highlights the potential value that a practice theory lens has for exploring gendered social practices and broadening understandings of notions of acceptable and suitable practice performance.